Temporopolar epilepsy stereoEEG: implant technique and outcomes - Maya A. Jayaram; Andrew I. Yang; Ashley L.B. Raghu; Peter A. Rozman; Denise F. Chen; Jon T. Willie; Ammar Kheder; Robert E. Gross (Epilepsy & Behavior Reports)
The temporal pole (TP) is an under-investigated region in temporal lobe epilepsy, often overlooked during stereoEEG (sEEG) due to the lack of characteristic Phase 1 findings and technical limitations in implanting using traditional orthogonal trajectories. We retrospectively reviewed consecutive patients with TP-onset seizures confirmed on sEEG. Two non-orthogonal trajectories were utilized targeting the inferior (iTP) and superior (sTP) aspects of TP. TP was implanted in 43 hemispheres of 30 patients, in whom seizure onset in TP was identified in 32 hemispheres. Seizure foci were spatially limited to TP in 50 % of cases, whereas the remainder involved broader regions, most commonly mesial temporal structures (88 %). In a subset of cases (22 %), TP seizures emerged from either the sTP or iTP, in contrast to those emerging more diffusely across both sub-regions. Encephaloceles were found in 43 % of patients and were associated with ipsilateral TP-onset seizures in 93 % of those cases. In a heterogeneous cohort who underwent surgical intervention, 50 % achieved Engel class I outcomes at 2 years. Our series illustrates the considerable variability in the seizure onset zone across patients with TP epilepsy, both within TP as well as in its involvement of neighboring regions. Inclusion of TP during invasive monitoring can inform subsequent surgical interventions.